Teachers’ TPACK Practice of English Blended Learning Course in the Midst of COVID-19 Pandemic - Yatun Yatun; Ahmad Munir; Pratiwi Retnaningdyah (Linguistic, English Education and Art (LEEA) Journal, 2021)
This study aims to examine teachers’ TPACK knowledge in practice that used in blended-learning course. This study employs a qualitative descriptive research design to analyze phenomena in the teaching and learning process. The observation focused on the three components of TPACK in practice included technological tool, content material, and learning activity. Furthermore, the finding shows that teachers promoted 22 and 24 of the 33 TPACK criteria in practice, which represented the TPACK knowledge. This means teachers have achieved more than 50 % of criteria which representing the TPACK knowledge in practice. In conclusion, the TPACK knowledge help teachers conducted an effective teaching with technology as teachers were able to apply the framework of TPACK in practice during the blended learning activity. Keywords: Blended-learning, Content Knowledge, Pedagogical knowledge Teachers’ Knowledge, Technological Knowledge, Technology Integration TPACK